Trends in time‐loss injuries during the 2011‐2016 South African Rugby Youth Weeks. (10th April 2018) - Sewry, N.; Verhagen, E.; Lambert, M.; van Mechelen, W.; Marsh, J.; Readhead, C.; Viljoen, W.; Brown, J.
Abstract : Youth rugby is a popular sport in South Africa (SA) with a high injury incidence. The annual SA Rugby Youth Week tournaments attract the top age‐group players in the country providing a sample of players for reliable injury surveillance. The aim of the study was to analyze the changes in time‐loss injury rates at the SA Rugby Youth Week tournaments between 2011 and 2016, differences between age‐groups, and to investigate associated injury risk factors. All confirmed time‐loss injuries at the 4 age‐group tournaments (under‐13, under‐16, and 2 under‐18) from 2011 to 2016 were recorded. Injury incidence densities (IID) for years, tournaments, and injury risk factors were calculated and Poisson regression analyses were performed to determine differences. Time‐loss injuries (n = 494) were reported over 24 240 exposure hours, with an overall IID of 20.4 (18.6‐22.2) injuries per 1000 player hours. The year 2013 had a significantly lower IID compared to 2011. Injury risk decreased with increasing age; under‐13 and under‐16 had significantly higher IID compared to under‐18 Craven Week. Tackling was the phase of play at highest risk, with an IID of 7.4 (6.3‐8.5) injuries per 1000 player hours. Central/peripheral nervous system (CNS/PNS) and, therefore, the head/neck were the most commonly occurring injuries/location injured. In conclusion, within the SA Rugby tournament structure, the older players had a decreased rate of injury. The tackle event was still the phase of play with the highest injury incidence regardless of age. This increase in incidence is largely due to an increase in CNS/PNS injuries.